The impact of environmental factors on the transport and survival of pathogens in agricultural soils from karst areas of Yunnan province, China: Laboratory column simulated leaching experiments - Ning, Zhuo; Wang, Shuaiwei; Guo, Caijuan; Zhang, Min (Frontiers in Microbiology, 2023)
Introduction Groundwater is considered the best candidate for drinking water supply in the karst area. The groundwater water resources, however, are vulnerable to pathogenic microorganism contamination because of the typically thin soil layers overlying aquifers and the high permeability of the aquifer host rock, resulting in short residence times and low natural attenuation capacities. Until now, little attention has been paid to the critical environmental factors affecting the pathogenic microorganism contamination in soil-groundwater systems in the karst area. Methods In the study, orthogonality column experiments with controlling ambient temperatures, pH values of inlet water, and soil porosities were carried out to investigate the transport and lifespan of pathogenic microorganisms in the leachate of agricultural soils in the karst area of Yunnan province, China. The pathogenic indicators, i.e., total bacteria count (TBC) and total coliforms count (TCC), and hydrochemical parameters, i.e., pH and permanganate index (CODMn) in the leaching water, were systematically monitored. Results and Discussion The results showed that bacteria including coliforms can survive for prolonged periods of time in karst soils. The soils overlying the karst rocks were unable to impede the bacteria from seeping into the groundwater. The soils, in turn, likely served as both reservoirs and incubators for pathogenic bacteria. The ambient temperature was the most predominant influential factor affecting both TBC and TCC. The bacteria concentrations were proportional to the temperature in the leachate. Therefore, more attention should be paid to temperature variations in protecting the water supply, particularly in the high-temperature period, such as during the summer months.